Use of Copper as A Converter Catalyst on Motorcycle Exhaust to Reduce Hydrocarbon (Hc) Emissions - Naniek Ratni Juliardi AR; Dimas Hafiizh Wicaksono (Future Science, 2023)
The number of vehicles especially in Surabaya, the increasing number of transportation means resulting in congestion in light traffic and a lot of gas CO, CO2, SOx, NOx and HC produced in wheeled motorcycles. Has a very real influence on the health of living things, so special studies are needed. Copper catalyst design is the most effective in reducing HC motor vehicle gas. The purpose of this study is to use a copper catalyst design method that is varied with engine speed (rpm) 1000, 3000, 5000, 8000, type of fuel, and uses the number of skates 1, 3, 5. The result From the best condition at 8000rpm and 5 skates result of HC gas reduction from premium fuel and the design with skat 5 and at rpm 8000 octane values 88 can reduce HC (96,7%), then the use of pertalite type fuel with 90 octane values, using 5 skat catalyst converters and engine speed at 8000 rpm the HC gas results are (40% ), use the first petrol pertamax with 92 octane values, use 5 skates and engine speed at 8000 rpm get HC gas results of (42%).